Bacterial Tomato Pathogen Ralstonia solanacearum Invasion Modulates Rhizosphere Compounds and Facilitates the Cascade Effect of Fungal Pathogen Fusarium solani - Lv Su; Lifan Zhang; Duoqian Nie; Eiko E. Kuramae; Biao Shen; Qirong Shen (Microorganisms, 2020)
Soil-borne pathogen invasions can significantly change the microbial communities of the host rhizosphere. However, whether bacterial Ralstonia solanacearum pathogen invasion influences the abundance of fungal pathogens remains unclear. In this study, we combined high-throughput sequencing, qPCR, liquid chromatography and soil culture experiments to analyze the rhizosphere fungal composition, co-occurrence of fungal communities, copy numbers of functional genes, contents of phenolic acids and their associations in healthy and bacterial wilt-diseased tomato plants. We found that R. solanacearum invasion increased the abundance of the soil-borne pathogen Fusarium solani. The concentrations of three phenolic acids in the rhizosphere soil of bacterial wilt-diseased tomato plants were significantly higher than those in the rhizosphere soil of healthy tomato plants. In addition, the increased concentrations of phenolic acids significantly stimulated F. solani growth in the soil. Furthermore, a simple fungal network with fewer links, nodes and hubs (highly connected nodes) was found in the diseased tomato plant rhizosphere. These results indicate that once the symptom of bacterial wilt disease is observed in tomato, the roots of the wilt-diseased tomato plants need to be removed in a timely manner to prevent the enrichment of other fungal soil-borne pathogens. These findings provide some ecological clues for the mixed co-occurrence of bacterial wilt disease and other fungal soil-borne diseases.